Atezolizumab in combination with bevacizumab and chemotherapy versus bevacizumab and chemotherapy in recurrent ovarian cancer – a randomized phase III trial (AGO-OVAR 2.29/ENGOT-ov34). Issue 12 (30th June 2020) - Harter, Philipp; Pautier, Patricia; Van Nieuwenhuysen, Els; Reuss, Alexander; Redondo, Andres; Lindemann, Kristina; Kurzeder, Christian; Petru, Edgar; Heitz, Florian; Sehouli, Jalid; Degregorio, Nikolaus; Wimberger, Pauline; et al.
Abstract : Background: Improvement in clinical outcomes of patients with platinum-resistant disease is an unmet medical need and trials in this population are urgently needed. Checkpoint-inhibitors have already shown activity in multiple other tumor entities and ovarian cancer, especially in the combination with anti-angiogenic treatment. Primary objective: To test if the activity of non-platinum-based chemotherapy and bevacizumab could be improved by the addition of atezolizumab. Study hypothesis: The addition of atezolizumab to standard non-platinum combination of chemotherapy and bevacizumab improves median overall survival from 15 to 20 months. Trial design: Patients are randomized to chemotherapy (paclitaxel weekly or pegylated liposomal doxorubicin) + bevacizumab + placebo vs chemotherapy + bevacizumab + atezolizumab. Stratification factors are: number of prior lines, planned type of chemotherapy, prior use of bevacizumab, and tumor programmed death-ligand 1 (PD-L1) status. Major inclusion/exclusion criteria: Recurrent epithelial ovarian, fallopian tube, or primary peritoneal cancer with up to three prior therapies and a treatment-free interval after platinum of less than 6 months. Patients with three prior lines of chemotherapy are eligible irrespective of the platinum free-interval. A de novo tumor tissue sample biopsy for determination of PD-L1 status prior to randomization for stratification is mandatory. Major exclusion criteria consider bevacizumab-specific and immunotherapy-specific criteria. Primary endpoint: Overall survival and progression-free survival are co-primary endpoints. Sample size: It is planned to randomize 664 patients. Trial registration: NCT03353831 .